Strength analysis of laminated glass/EVA interfaces: Microstructure, peel force and energy of adhesion. (1st October 2022) - Bornemann, Steffen; Henning, Sven; Naumenko, Konstantin; Pander, Matthias; Thavayogarajah, Nishanth; Würkner, Mathias
Abstract: The aim of this study is to analyze the adhesive strength of laminated glass with an interlayer material based on ethylene-vinyl acetate (EVA) copolymer. To investigate the microstructure within the entire cross-section of glass laminates, cryo-fracture surfaces of the samples were prepared. SEM images illustrate the boundary layers on the glass surfaces with the thicknesses within the range from few nm to 100 μ m . Tensile and 180 ∘ peel tests were performed to estimate the adhesive strength. No significant differences in peel force values were obtained for the EVA/tin side and EVA/air side interfaces. A direct approach to evaluate the energy of adhesion based on the results of tensile tests and peel tests is developed. The evaluated energy of adhesion is nearly the same for temperatures of 20 °C and 40 °C and increases by a factor of 2 for the temperature of −20 °C.